2014
DOI: 10.1002/iub.1268
|View full text |Cite
|
Sign up to set email alerts
|

ST6GalNAcII mediates the invasive properties of breast carcinoma through PI3K/Akt/NF‐κB signaling pathway

Abstract: Metastasis of tumor cells is the most deadly attribute of breast cancer patients. Aberrant sialylation is closely associated with malignant phenotype of tumor cells, including invasiveness and metastasis. The objective of this study is to clarify the possible role and mechanism of ST6GalNAcII in the metastasis process of breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Mounting evidence demonstrated that the alterations of sialylation and the levels of ST activities derived from cancer cells were relevant to breast cancer invasion and metastasis. 28, 29 Here, we indicated that the ST profiling patterns were significantly different in breast cancer tissues to adjacent tissues. Among these, the expression of ST6GALNAC5 , ST8SIA3 and ST8SIA4 was significantly upregulated in breast cancer tissues compared with adjacent tissues, and ST8SIA2 and ST8SIA6 were upregulated in the adjacent tissues.…”
Section: Discussionmentioning
confidence: 74%
“…Mounting evidence demonstrated that the alterations of sialylation and the levels of ST activities derived from cancer cells were relevant to breast cancer invasion and metastasis. 28, 29 Here, we indicated that the ST profiling patterns were significantly different in breast cancer tissues to adjacent tissues. Among these, the expression of ST6GALNAC5 , ST8SIA3 and ST8SIA4 was significantly upregulated in breast cancer tissues compared with adjacent tissues, and ST8SIA2 and ST8SIA6 were upregulated in the adjacent tissues.…”
Section: Discussionmentioning
confidence: 74%
“…As proved, p-Akt 308 and p-Akt 473, the phosphorylation of Akt, promoted tumor invasion and chemoresistance of breast carcinoma. 38, 39 In this article, when siAkt was utilized to inhibit the expression of p-Akt 308 and p-Akt 473 in breast cancer, the capability of cell migration, invasion and proliferation was significantly attenuated, indicating that the phosphorylation of Akt did have a role in the progression of breast cancer. Taken together, miR-106b and miR-93 mediated cell migration, invasion and proliferation by suppression of PTEN via PI3K/Akt pathway in breast cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Changes in cell surface glycosylation have been shown to increase tumorigenesis and metastasis (Ohtsubo and Marth, 2006; Ren et al, 2014; Tamura et al, 2014; Tarp and Clausen, 2008; Taylor-Papadimitriou et al, 1999). The most prevalent aberrant glycoforms found in cancer are the Tn (GalNAc α 1-O-Ser/Thr) and sialyl-Tn (STn) (NeuAc α 2-6-GalNAc α 1-O-Ser/Thr) glycoforms (Springer, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic conditions often found in tumors might alter expression of glycosyltransferases (Kannagi et al, 2010), including sialyltransferases such as ST6GalNAcI to create sialyl-Tn antigens. Glycosylation changes also alter cell adhesion and motility, which increase the metastatic potential of the tumor cell (Gill et al, 2013; Radhakrishnan et al, 2014; Ren et al, 2014; Tamura et al, 2014). Tn and STn antigen expression is correlated with adverse outcome and decreased patient survival in breast cancer, gastric cancer, endometrial cancer, and oral squamous cell carcinoma, among other cancers (Cazet et al, 2010; Itzkowitz, 2003; Lin et al, 2014; Ohno et al, 2006; Victorzon et al, 1996).…”
Section: Introductionmentioning
confidence: 99%